From Near and Far : A Transnational History of France - Stovall, Tyler, 1954-2021 (Book collections on Project MUSE., 2023)
"From Near and Far relates the history of modern France from the French Revolution to the present. Noted historian Tyler Stovall considers how the history of France interacts with both the broader history of the world and the local histories of French communities, examining the impacts of Karl Marx, Ho Chi Minh, Paul Gauguin, and Josephine Baker alongside the rise of haute couture and the contemporary role of hip hop.From Near and Far focuses on the interactions between France and three other parts of the world: Europe, the United States, and the French colonial empire. Taking this transnational approach to the history of modern France, Stovall shows how the theme of universalism, so central to modern French culture, has manifested itself in different ways over the last few centuries. Moreover, it emphasizes the importance of narrative to French history, that historians tell the story of a nation and a people by bringing together a multitude of stories and tales that often go well beyond its boundaries. In telling these stories From Near and Far gives the reader a vision of France both global and local at the same time. "--